Hubungan Penggunaan Antidiabetes Oral terhadap Nilai Klirens Kreatinin pada Pasien Diabetes Melitus Tipe 2 di Rumah Sakit Umum di Jakarta - Dini Permata Sari; Hanan Al Jabri (JURNAL FARMASI DAN MAKANAN, 2024)
Diabetes mellitus can cause various complications such as stroke, coronary heart disease, peripheral artery disease, retinopathy, neuropathy and nephropathy. Choosing the right drug in diabetes mellitus patients is very important because most antidiabetic drugs are excreted through the kidneys, so it is necessary to monitor creatinine clearance values as an indicator of impaired kidney function. The aim of this research is to find out the relationship between the use of oral antidiabetics and creatinine clearance values ​​in type 2 diabetes mellitus. This research is an observational analytical study with a cross-sectional data collection method on patients type 2 diabetes mellitusbetween January 2023 - December 2023 at a public hospital in Jakarta. This study obtained 39 patients, including the majority of patients who used oral anti-diabetics were women, 56.4%.The largest age was in the range 46 – 55 years at 38.5%. The most common type of drug is a combination of two drugs glimepirid + metformin as much as 35.9% and the creatinine clearance value in type 2 diabetes mellitus patients is a klirens kreatinin value < 90 mL/min/1.73m2 of 66.7%. The results of the chi-square test obtainedp=0.093. Based on the values obtained, there was no significant relationship between the use of oral antidiabetics and creatinine clearance values.